Targeting androgen receptor and PIP5K1A in prostate cancer cells using CRISPR-Cas9 genome editing tool - Hernández-Quiles, Miguel (2017)
According to the World Cancer Research statistics, Prostate Cancer (PCa) accounts for 15% of all new cancer cases in men every year. More than 30% of treated patients will suffer disease recurrence and will develop Castration Resistant Prostate Cancer (CRPC), which no longer responds to androgen deprivation therapies. The mechanisms underlying the development of CRPC remain unclear. Androgen Receptor (AR) is highly expressed in prostate cancer cells, and plays an essential role in growth, survival and differentiation of prostate tumours. The aberrant activation of AR and AR-variants lacking the ligand binding domain (LBD), which is the therapeutic target of most PCa treatments, are characteristics of CRPC. In addition, recent studies suggest that PIP5K1A, a lipid kinase responsible for the synthesis of PIP2, might play an important role in PCa tumourogenesis and AR activation. In this study we used CRISPR-Cas9 genome editing technology to target AR and PIP5K1A in LNCaP C4-2 prostate cancer cells. Following cell sorting of GFP+ cells and clonal expansion, we successfully generated 9 mutant cell lines for PIP5K1A and 3 for AR. PCR Genotyping and DNA sequencing confirmed the presence of indels in targeted alleles in all of these clones, and Western Blots indicated that disruption of the targeted gene expression was achieved in several clones. Preliminary data showed AR depletion also reduces PIP5K1A expression, suggesting a regulatory pathway involving these genes. The AR and PIP5K1A mutant clones will be useful cell models to explore mechanisms involved in CRPC, and thus may aid the search of new therapies.